(untitled) (Interdisciplinary Studies Journal, 2025)
Despite advances toward gender equality and discussions on gender and sexuality, our society is still marked by a cisheteronormative norm that marginalizes and renders dissident experiences invisible. Considering the school as a reflection and microcosm of society, it becomes crucial to address these issues in educational spaces. This research identifies, through discursive positions, the challenges and support experienced by the LGBTQIA+ community at the Rio Grande campus of the Federal Institute of Education, Science, and Technology of Rio Grande do Sul (IFRS). Specifically, it examines: (1) the sense of belonging to the campus among LGBTQIA+ students; (2) the profile of this community; and (3) proposed mitigation strategies for the identified challenges. Supported by a qualitative approach, data were collected through questionnaires voluntarily answered by campus students. Results indicate that while most feel welcomed, vulnerabilities persist. Many reported verbal or physical violence related to sexual orientation or gender identity; 26.67% stated that these incidents occurred on campus. Many feel protected, but 43.75% reported that this sense of safety varies depending on the environment. These findings highlight the importance of institutional actions to strengthen security and support, fostering debates and transformative actions regarding the challenges faced by the LGBTQIA+ community.